Uganda : Technical Assistance Report-Improving GDP Forecasting. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses recommendations for improving GDP forecasting in Uganda. GDP forecasting, ranging from a quarterly to a five-year horizon, must be improved using the tools that are now available at the Ministry of Finance, Planning and Economic Development (MoFPED). The five-year forecast can be fruitfully used in the medium-term projections of government revenue, deficit and debt. The short-term forecasts should be systematically integrated within the (annual) sectoral forecasts currently being done at the MoFPED. While considering the set of tools under development, the IMF mission recommends the deployment of these tools in a more urgent manner, to stimulate learning-by-doing of local staff.